2016
DOI: 10.1007/s13594-016-0279-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial spores isolated from ingredients, intermediate and final products obtained from dairies: thermal resistance in milk

Abstract: The ingredients used for the development and production of milk-based products pose the risk of the introduction of new, emerging spore-formers producing highly thermoresistant spores. Therefore, the aim of this study was to examine the heat resistance of spores isolated from dehydrated ingredients, intermediate and final products. Furthermore, the influence of the heating medium (milk or phosphate buffer) on the heat resistance was determined in order to assess which medium is best to use in the context of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Also, B. cereus, B. circulans and B. pumilus were isolated with percentage of 16.7, 13.3 and 20% in infant milk formulae, respectively [ 31 ]. B. smithii was isolated from diverse food products obtained from local dairies such as cocoa powder, milk powder and dessert products [ 80 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Also, B. cereus, B. circulans and B. pumilus were isolated with percentage of 16.7, 13.3 and 20% in infant milk formulae, respectively [ 31 ]. B. smithii was isolated from diverse food products obtained from local dairies such as cocoa powder, milk powder and dessert products [ 80 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…However, Margosch et al (2004) found that the fermentation media can severely affect the heat resistance of the bacteria. Stoeckel et al (2016) also found that the heat tolerance of B. smithii spores in milk is different from that of spores in phosphate buffer salts, with spores in phosphate buffer being more heat resistant, and that the media can greatly influence the physiological characteristics of the bacteria, all of which could be taken into account for subsequent consideration in culture optimization.…”
Section: Culture Optimizationmentioning
confidence: 99%
“…Beyond the contribution of raw milk itself, another important source of spores is ingredients used in the manufacture of processed dairy products ( Stoeckel et al, 2016 ). For example, cocoa powder mixes (typically composed of cocoa powder, sucrose [or other sugar], starches, gums, flavorings, and so on) have been shown to contribute high levels of spores to chocolate milk and other chocolate-flavored dairy products (e.g., chocolate ice cream mix; Douglas et al, 2000 ; Cadirci et al, 2018 ).…”
mentioning
confidence: 99%
“…While raw milk is still an important source of spores in milk and whey powders, thermophilic spores may also originate from biofilms in processing equipment (e.g., separators, heat exchangers, and evaporators) that are not adequately cleaned and sanitized ( Flint et al, 2020 ) as the conditions inside dairy powder processing equipment is ideally suited to select for thermophiles ( Seale et al, 2015 ). The use of dried dairy ingredients in reconstituted and heat-treated beverages (e.g., sports beverages, nutritional beverages, and so on) is of particular importance because obligate thermophiles represent a major proportion of the spore contaminants in many dairy powders ( Yuan et al, 2012 ; Miller et al, 2015 ) and spores of these organisms exhibit much higher heat resistance than other groups of spores ( Stoeckel et al, 2016 ), potentially leading to spore survival during UHT processing in end product applications. Additionally, nondairy ingredients including spices, dried herbs, vanillin, stabilizers, egg products, and so on have all been shown to be important potential sources of spores in processed dairy products ( Lücking et al, 2013 ).…”
mentioning
confidence: 99%